The Streptococcus pneumoniae pezAT toxin-antitoxin system reduces β-lactam resistance and genetic competence - Wai Ting Chan; Manuel Espinosa (Frontiers in Microbiology, 2016)
Chromosomally-encoded Type II Toxin-Antitoxin operons are ubiquitous in bacteria and archaea. Antitoxins neutralize the toxic effect of cognate Toxins by protein-protein interactions and sequestering the active residues of the Toxin. Toxins target essential bacterial processes, mostly translation and replication. However, one class apart is constituted by the PezAT pair because the PezT toxin target cell wall biosynthesis. Here we have examined the role of the pezAT toxin-antitoxin genes in its natural host, the pathogenic bacterium Streptococcus pneumoniae. The pezAT operon on Pneumococcal Pathogenicity Island 1 was deleted from strain R6 and its phenotypic traits were compared with those of the wild type. The mutant cells formed shorter chains during exponential phase, leading to increased colony-forming units. At stationary phase, the mutant was more resilient to lysis. Importantly, the mutant exhibited higher resistance to antibiotics targeting cell walls (β-lactams), but not to antibiotics acting at other levels. In addition, the mutants also showed enhanced genetic competence. We suggest that PezAT participates in a subtle equilibrium between loss of functions (resistance to β-lactams and genetic competence) and gain of other traits (virulence).